La population totale du Canada depuis 1600 - Hamelin, Louis-Edmond (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1965)
An attempt is made to calculate the population of Canada since the period of discovery. The author bas made a few corrections to official statistics and bas added the figures for Newfoundland (prior to 1949) and for the Indians and Eskimos (prior to 1851). Throughout it is a question of the same territory, that of present-day Canada.Visualized in this fashion, the history of the population of Canada falls into jour periods :1. 1600-1710 : The total population declined because the slow increase in European immigrants did not compensate for the decrease in numbers of indigenous peoples ;2. 1710-1775 : The total population grew slowly during this period but, after two centuries of colonisation, Canada remained a land of Indians ;3. In less than a century the total population soared from 300,000 to 3,000,000 ; never would Canada experience an equally long period characterized by such a high rate of demographic expansion. Canada became British ;4. The present century bas seen jour demographic periods ; rapid increase took place during two of these periods : 1896-1914 and since 1942.The alternation of rates of growth emphasizes the sensitivity of the Canadian economy to both external and internal events.